2022
DOI: 10.3389/fneur.2022.884519
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Changes During Mechanical Thrombectomy for Acute Ischemic Stroke Are Associated With Serious Early Treatment Complications: Symptomatic Intracerebral Hemorrhage and Malignant Brain Edema

Abstract: BackgroundSymptomatic intracranial hemorrhage (sICH) and malignant brain edema (MBE) are well-known deleterious endovascular treatment (EVT) complications that some studies found to be associated with postprocedural blood pressure (BP) variability. We aimed to evaluate their association with periprocedural BP changes, including its intraprocedural decrease.MethodsWe retrospectively analyzed the data of 132 consecutive patients that underwent EVT between 1 December 2018 and 31 December 2019, for anterior circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, our prospective study showed that 22.6% of patients developed MBE, which is similar to data from a retrospective analysis of 130 patients (25.6% of patients with MBE) [5]. Furthermore, previous clinical studies have found several predictive factors for the presence of MBE in patients following EVT [5,6,25,26]. These factors included advanced age, fasting blood glucose, hypertension, baseline NIHSS score, ASPECT score, collateral score, and unsuccessful recanalization.…”
Section: Discussionsupporting
confidence: 87%
“…However, our prospective study showed that 22.6% of patients developed MBE, which is similar to data from a retrospective analysis of 130 patients (25.6% of patients with MBE) [5]. Furthermore, previous clinical studies have found several predictive factors for the presence of MBE in patients following EVT [5,6,25,26]. These factors included advanced age, fasting blood glucose, hypertension, baseline NIHSS score, ASPECT score, collateral score, and unsuccessful recanalization.…”
Section: Discussionsupporting
confidence: 87%
“…Interaction between general anesthesia and collateral flow in the reperfusion injury through blood pressure changes and progression of penumbra to ischemic core is complex and not fully understood. [16][17][18] Every efforts should be made to define the best intra-and post-operative hemodynamic management during anesthesia in a special setting such as the one of patients obtaining first-pass complete recanalization. Procedure time is influenced by a significant large number of variables, including those related to stroke etiology, such as clot composition, length, and shape.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that a lower systemic BP prior to symptomatic vessel recanalization limits collateral flow and perfusion of penumbral tissue, leading to larger post-intervention infarct volumes and poorer functional treatment results [7,8]. Recently, one study showed that intraprocedural hypotension can lead to serious EVT treatment complications, such as malignant brain edema and symptomatic intracranial hemorrhage, which may be further mediators of worse clinical outcomes [9].…”
Section: Introductionmentioning
confidence: 99%